2019
DOI: 10.3389/fpsyt.2019.00749
|View full text |Cite
|
Sign up to set email alerts
|

Response and Remission Rates in Internet-Based Cognitive Behavior Therapy: An Individual Patient Data Meta-Analysis

Abstract: Background: Internet-delivered cognitive behavior therapy (ICBT) was developed over 20 years ago and has since undergone a number of controlled trials, as well as several systematic reviews and meta-analyses. However, the crucial question of response rates remains to be systematically investigated. The aim of this individual patient meta-analysis (IPDMA) was to use a large dataset of trials conducted in Sweden to determine reliable change and recovery rates across trials for a range of conditions. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 91 publications
3
37
1
Order By: Relevance
“…Our findings corroborate previous findings of symptom severity, education, age, medication use, and PRSs as predictors for ICBT outcomes. 3 8 10 12 13 16 19 Regarding remission of MDD in particular, our result is in line with Andersson and colleagues 11 in that depression symptom severity and higher anxiety predicted the outcome. Interestingly, the number of predictors that our final model settled with was fairly high (n = 45), also consistent with the logic of a multi-modal approach for predicting complex traits and behaviours.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings corroborate previous findings of symptom severity, education, age, medication use, and PRSs as predictors for ICBT outcomes. 3 8 10 12 13 16 19 Regarding remission of MDD in particular, our result is in line with Andersson and colleagues 11 in that depression symptom severity and higher anxiety predicted the outcome. Interestingly, the number of predictors that our final model settled with was fairly high (n = 45), also consistent with the logic of a multi-modal approach for predicting complex traits and behaviours.…”
Section: Discussionsupporting
confidence: 89%
“…6 7 However, a substantial portion of individualsestimates range from 10 to 60%do not respond sufficiently to ICBT. 8 9 As there is room for improvement, researchers have begun to investigate what variables predict symptom reduction, 3 8 10 remission status, 11 and other outcomes proximal to ICBT response such as adherence, 12 and dropout. 13 Identifying replicable predictors could inform clinical decision making allowing for better tailored intervention and care for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Different criteria for defining responders are used in different studies making comparisons to other studies difficult (Loerinc et al, 2015). However, the effects reported in this thesis are similar to those reported in a large study on clinical effects of ICBT treatments concluding that about one third reach remission post-treatment (Andersson, Carlbring, & Rozental, 2019). In a meta-analysis examining response rates in face-to-face treatment the response rate of CBT for GAD was 47% on average (Loerinc et al, 2015).…”
Section: Outcome Measures and Diagnosissupporting
confidence: 73%
“…A meta-analysis of 29 Swedish studies including 2866 patients treated with ICBT for anxiety disorders, depression, and other disorders revealed that 65.6% of all patients improved, with one-third achieving remission. [ 3 ] As digital approaches to mental health increase, there is also space for artificial intelligence (AI) to be used to predict or detect or treat mental health issues. This can be incorporated into digital modalities via cell phone apps which can personalize mental health care and natural language, and access to data use can lead to formulation of conversation assistants online as well to be used for therapeutic intervention.…”
Section: Digital Interventionsmentioning
confidence: 99%